Chili ( Capsicum annuum L.) genotypes resistant to Pepper yellow leaf curl Thailand virus (PepYLCTHV) - Patcharaporn Suwor; Tawatchai Masirayanan; Hathairat Khingkumpungk; Wen Shi Tsai; Kanjana Saetiew; Suchila Techawongstien; Sanjeet Kumar; Somsak Kramchote (Journal of Plant Protection Research, 2023)
Pepper yellow leaf curl Thailand virus (PepYLCTHV) causes leaf curl disease in chili pro- duction regions of the tropics and subtropics. Information on PepYLCTHV disease severi- ty and resistance in chili pepper is still limited in Thailand. This study reports PepYLCTHV disease severity through graft inoculation and selection of single resistant plants for use in a chili breeding program. Twenty-one chili genotypes consisting of the local cultivar (5) collected from Thailand, breeding lines (9) developed at Khon Kaen University (KKU), Thailand and improved lines (7) obtained from the World Vegetable Center, Taiwan were used in this study. Forty-five-day-old seedlings of all the genotypes were graft inoculated with PepYLCTHV in a randomized complete block design (RCBD) with three replications and 10 plants per replication and kept in a plastic net house. Disease symptoms were scored at 20, 27, 34, 41 48, and 55 days after graft/inoculation (DAI). Disease severity was visually recorded using 0−5 scores. Results showed that the disease severity of 21 chili genotypes significantly differed at 48 days after grafting. High resistance and stability were shown by 9853-123 genotypes. Two genotypes, PSP11-7 and PSP11-10-1, showed resistant reaction with disease severity scores of 1.9 and 1.8, respectively. However, among 21 chili geno- types or 630 grafted plants, 302 plants were successfully grafted inoculated plants. There- fore, from the results of this work, highly resistant plants (69 single plants) can be selected, selfed and advanced for breeding.
Keywords: Plant Virus Research Studies; Agricultural Practices and Plant Genetics; Agricultural pest management studies